Performance Evaluation of Rice Combine Harvester based on Thai Industrial Standard - Yooprasobchoke, Julalak (วารสารสมาคมวิศวกรรมเกษตรแห่งประเทศไทย, 2016)
This research entitle “performance evaluation of rice combine harvesters based on Thai industrial standard” was aimed to evaluate the performance test based on Thai industrial standard 1428-1997. Five model of kubota rice combine harvesters were tested composed of DC60, DC68G, DC70, DC70G and DC95GM, respectively. The tests were conducted at Pathumthaini Rice Research Centre. Based on the test results of DC60, it was found that the effective field capacity was 3 rai hr-1, the fuel consumption was 3.9 l rai-1and the total field loss was 6 . 9%. The effective field capacity, fuel consumption and total field loss of DC68G were 3.95 rai hr-1, 2.2 l rai-1 and 2 . 1%, respectively. Where as the effective field capacity, fuel consumption and total field loss of DC70 were 4.5 rai hr-1, 1.2 l rai-1and 2.5%, respectively. For DC70G, they were 4.5 rai hr-1, 2.7 l rai-1 and 2%, respectively. The perforamance test results of DC95GM were 6.2 5 rai hr-1, 1.1 l rai-1 and 1.8%, respectively.Based on the economic analysis, it was found that the break even point of the machines was 252, 156, 109, 147and 117 hr yr-1, respectively. Considering the contract rate as 500 Baht rai-1, the pay back period was found to be 2.92, 1.74, 1.18, 1.63 and 1.28 yr, respectively.